Surface film formation on Mg electrode containing magnesium polysulfides in TFSI-based electrolytes - Bracamonte, Maria Victoria (2023)
A rechargeable magnesium sulfur battery is an attractive redox couple due to the natural abundance of electrode active components and the possibility to offer a suitable energy density at a low price. The sulfur conversion mechanism in the magnesium battery is well known, however, several issues such as the large overpotential, fast capacity fading, and slow reaction kinetics are still under debate and should be properly addressed. At least partially, these problems are related to the passivation of the magnesium surface, due to the interaction with electrolyte/catholyte. Here, we explore the Mg2+ deposition/dissolution process on the Mg metal electrode in the presence of Mg(TFSI)2/MgCl2 in TEGDME:DOL and MgS8/Mg(TFSI)2/MgCl2 in TEGDME:DOL electrolytes. We show that an interfacial layer in the presence of polysulfides is less resistive, due to the joint corrosion nature of chlorides and sulfides. This has been confirmed in a combined study using conventional electrochemical experimental techniques supported by modeling of EIS spectra, X-ray photoelectron spectroscopy (XPS), and focused ion beam-scanning electron microscopy (FIB-SEM).